Mergers and Acquisitions and CEO’s Mind Mapping - Manas Mayur, Leona Pereira (International Journal of Scientific Research and Management (IJSRM), 2014)
The purpose of this research is to take a peep into the mind of CEO’s with respect to mergers and acquisitions. Mergers happen frequently. Why do these mergers occur? Some CEO’s undertake mergers their rational counterparts would not. Merger consequences are dwelled upon much more that the merger motives in the first place. These motives are often less investigated. Although there exist enormous influence of the individual managers involved with M&A process, remarkably little literature exists to study the actions of those managers and CEO’s. Keywords: